(untitled) (Journal of the College of Basic Education, 2022)
Banks provide many services through modern electronic means of communication, and the multiplicity of means of communication provided by the use of electronic communication networks raise legal issues because they may relate to more than one legal system. The electronic banking service may generate a relationship purely or may generate a relationship of an international nature linked to more than a legal system, so it is necessary to know the electronic service and the legal system to which this service. Based on the foregoing, the research was divided into three topics. The first section discusses the electronic banking services, which includes a statement to introduce these services and the advantages and disadvantages of electronic banking. In the third section, we deal with the determination of the law in accordance with international conventions and arbitration rules